Pengaruh Kualitas Pelayanan dan Fasilitas Hotel Terhadap Minat Berkunjung dengan Kepuasan Pengunjung sebagai Variabel Intervening: Studi Kasus pada Tamu Hotel UP Peak Semarang - Aji Pratama; Rauly Sijabat; Ratih Hesty Utami Puspita (Journal of Management and Social Sciences, 2024)
This study aims to analyze the impact of service quality and hotel facilities on visiting intention, with visitor satisfaction as an intervening variable, using the SEM AMOS application. The case study was conducted on guests at UP Peak Hotel Semarang. The research method used is path analysis and the Sobel test to examine the mediation effect. The results show that service quality has a positive impact on visitor satisfaction, but this impact is not significant. In contrast, hotel facilities have a positive and significant impact on visitor satisfaction. Furthermore, visitor satisfaction was found to have a negative and insignificant impact on visiting intention. Path analysis also shows that service quality does not have a significant direct impact on visiting intention, but facilities do have a positive and significant impact. The Sobel test indicates that visitor satisfaction acts as an intervening variable between service quality and facilities with visiting intention.